2021
DOI: 10.1093/mnras/stab280
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic merger rate density of compact objects: impact of star formation, metallicity, initial mass function, and binary evolution

Abstract: We evaluate the redshift distribution of binary black hole (BBH), black hole – neutron star binary (BHNS) and binary neutron star (BNS) mergers, exploring the main sources of uncertainty: star formation rate (SFR) density, metallicity evolution, common envelope, mass transfer via Roche lobe overflow, natal kicks, core-collapse supernova model and initial mass function. Among binary evolution processes, uncertainties on common envelope ejection have a major impact: the local merger rate density of BNSs varies f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 131 publications
8
132
0
1
Order By: Relevance
“…Together with another candidate of a black hole-neutron star binary merger GW190426_152155 (Abbott et al 2021a), we may now safely consider that black hole-neutron star binaries are actually merging in our Universe. The merger rate is currently inferred to be % 12-240 Gpc À3 yr À1 , which is largely consistent with previous theoretical estimation (Dominik et al 2015;Kruckow et al 2018;Neijssel et al 2019;Zevin et al 2020;Santoliquido et al 2021, see also Narayan et al 1991;Phinney 1991 for pioneering rate estimation). Unfortunately, despite the presence of neutron stars, no associated electromagnetic counterpart was detected.…”
supporting
confidence: 87%
“…Together with another candidate of a black hole-neutron star binary merger GW190426_152155 (Abbott et al 2021a), we may now safely consider that black hole-neutron star binaries are actually merging in our Universe. The merger rate is currently inferred to be % 12-240 Gpc À3 yr À1 , which is largely consistent with previous theoretical estimation (Dominik et al 2015;Kruckow et al 2018;Neijssel et al 2019;Zevin et al 2020;Santoliquido et al 2021, see also Narayan et al 1991;Phinney 1991 for pioneering rate estimation). Unfortunately, despite the presence of neutron stars, no associated electromagnetic counterpart was detected.…”
supporting
confidence: 87%
“…We find a mild preference for efficient CEs in our modeling, which strongly disfavors highly inefficient CEs with α CE 0.2. Inferred values for the CE efficiency α CE have more diversity than natal spins across the literature, from population modeling (e.g., Bavera et al 2020a;Santoliquido et al 2021;Zevin et al 2020) to hydrodynamical simulations (e.g., Fragos et al 2019) and theoretical considerations (e.g., Ivanova et al 2013). Our results, which mildly favor high CE efficiencies, are in agreement with Santoliquido et al (2021), who found high CE efficiencies are necessary to match the merger rate of binary neutron stars in their population models, and with Fragos et al (2019), who modeled the spiral-in phase of CE evolution using hydrodynamic simulations and found a non-negligible fraction of the envelope remains bound to the core after the CE is successfully ejected.…”
Section: Discussionmentioning
confidence: 99%
“…Inferred values for the CE efficiency α CE have more diversity than natal spins across the literature, from population modeling (e.g., Bavera et al 2020a;Santoliquido et al 2021;Zevin et al 2020) to hydrodynamical simulations (e.g., Fragos et al 2019) and theoretical considerations (e.g., Ivanova et al 2013). Our results, which mildly favor high CE efficiencies, are in agreement with Santoliquido et al (2021), who found high CE efficiencies are necessary to match the merger rate of binary neutron stars in their population models, and with Fragos et al (2019), who modeled the spiral-in phase of CE evolution using hydrodynamic simulations and found a non-negligible fraction of the envelope remains bound to the core after the CE is successfully ejected. These results for α CE contrast with those from Bavera et al (2020a), but we find that these conflicting results arise only from the consideration of more forma-tion channels in this work; when considering contributions from only the CE and SMT channels, we also favor low CE efficiencies of α CE 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…The details of these results might strongly depend on the star formation rate and metallicity evolution model, which can deeply change the merger rate [36,38,193,194]. We will investigate the impact of these quantities in a follow-up study.…”
Section: Comparison With Bbhs In Gwtc-2mentioning
confidence: 99%